THE MAIN PROBLEMS ARISING DURING THE TRANSLATION PROCESS - Sobirova Sabina Sanjar kizi (International Multidisciplinary Journal for Research & Development, 2026)
The article identifies the main problems arising during the translation process, their causes and ways to solve them. Inclusion of linguistic, cultural, terminological, contextual, style and technological problems and suggestions for practical use by professional translators and linguists are shown. The results demonstrate ways to raise the quality of translations and ways to improve the training in education process.